2021
DOI: 10.5219/1485
|View full text |Cite
|
Sign up to set email alerts
|

Сonsumer preferences on the market of plant-based milk analogues

Abstract: The consumption of plant-based food products instead of animal-based products tends to increase worldwide which can be caused by the global expansion of alternative food products. The article's objective is to investigate the perception of plant-based milk analogues by real and potential consumers and determine the prospects of increasing their assortment. The assortment of plant-based analogues of milk and products made thereof is analyzed. A projection of the almond milk sales was made as one of the most eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Hoek et al [ 33 ] also demonstrate that health perception also greatly influences the readiness to replace meat with plant-based meat. Prytulska et al [ 34 ] corroborate the significant impact of health consciousness on favoring PBM. Moreover, Martínez-Padilla et al [ 35 ] found that positive perceptions of PBM’s naturalness, health benefits, and nutritional parity to cow’s milk bolstered its consumption, whereas perceptions of PBM as excessively processed or synthetic deterred consumption.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Hoek et al [ 33 ] also demonstrate that health perception also greatly influences the readiness to replace meat with plant-based meat. Prytulska et al [ 34 ] corroborate the significant impact of health consciousness on favoring PBM. Moreover, Martínez-Padilla et al [ 35 ] found that positive perceptions of PBM’s naturalness, health benefits, and nutritional parity to cow’s milk bolstered its consumption, whereas perceptions of PBM as excessively processed or synthetic deterred consumption.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Although the random assignment to treatment means the two groups should not differ in any characteristic, we measured several covariates to ensure the groups were balanced and therefore increase the overall robustness. We assessed gender, because women are on average more open to plant-based food than men (Modlinska et al, 2020); hunger, because it can influence preferences toward high-calorie food (Lozano et al, 1999), and dairy milk might be perceived as more calorific than oat milk; age, as younger people are more open to plant-based milk alternatives (Prytulska et al, 2021); prevalence of consumers of plant-based milk among peers, since food choices can be influenced by peers (Lea & Worsley, 2001), especially at younger ages (Koehn et al, 2014); past behaviour (usual milk of choice), because past food choices are an important predictor of future ones (Köster, 2009;Wong & Mullan, 2009); environmental responsibility, because Bacon & Krpan (2018) found it can predict sustainable food choices.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the technical weight percentage graph show that the use of almond milk with a percentage of 28.66% is the most needed attribute followed by 12.9% the use of isolated soy protein in the development of almond soy milk coffee. According to a previous study, the properties of plant products that support health and reduce the negative impact on the environment that comes from the production of animal products are one of the factors in purchasing decisions [19]. Almond milk meets the highest consumer preference compared to oat and soy milk.…”
Section: Hoqmentioning
confidence: 99%